Projetos de extensão da Universidade Federal dos Vales do Jequitinhonha e Mucuri/Diamantina em escolas de educação básica: ações, concepções e desafios - Maria do Perpetuo Socorro de Lima Costa (2015)
This proposal stems from several concerns related to the university and society relationship, this being the issue addressed by the research, which, in turn, involves aspects related to extension actions at the University. The problem that orients this study, relates to base that sustain extension projects in basic education schools, inquiring about the ways in which present themselves them university-school relations translated between the actors involved in the extension, and the perspective of the two parties involved: on one end, the professors and staff of the elementary schools for whom these projects are developed and, on the other end, the professors and university students who implement the project in these schools. In other words, it is asked about the potentialities of such projects with regard to the discussion of Freire on extension practices as extension or as communication between subject to and groups. These questions were thought and extension projects presented and discussed by reports of its protagonists and dialogues with the discussion of Paulo Freire on extension or communication. What the projects represent to protagonists in the university and to school professionals is one dimension of analysis that says, with respect to significance and understanding that these actors possess and manifest in the understated, how they are understood or what is thought in their respect. In other words: what type of university students and teachers develop relationship with school professionals? To what extent they approach dialogical relations, extension of relationships and / or reveal to what extent other dynamic and configuration? Thus refers us to the perspectives and conceptions that guide and activities / methodologies by which the extension activities are held - that is, its dynamics, its resources, its objectives - and the origin of these projects: leave from the school community demand, of interest of those involved, university demands, or others who are? What difficulties and tensions are constituted in the development of the extension projects of UFVJM / Diamantina in schools? It is an empirical research with qualitative emphasis, and a case study of two projects. As an instrument of investigation, we conducted a documentary survey by means of an identification sheet of PROEXC after identifying what are the outreach projects developed by UFVJM graduate programs in public elementary schools. To identify the concerns of social actors with regard to university outreach, we conducted semi-structured interviews and participatory observation to hear the voices of these subjects, in relation to the interaction between university and school. To examine these questions and hypotheses, we presented a discussion concerning notions of outreach in the framework of outreach politics in public institutions of undergraduate education, among them UFVJM/Diamantina. We have elected Paulo Freire as a central reference for discussing the dimensions of interactions between university and school and other study questions, from the fundamentals that presents in his book Comunicação or Extensão (2011) since these contribute significantly to the understanding of the modes of interaction and how that interferes significantly in the "thinking" and "doing" university extension, and in the determination of extension of of action intentionality. At the same time, other considerations contribute to this study, including the discussion and proposition by Paulo Freire, with respect to this issue, and the guidelines as defined by FORPROEX in the Plano Nacional de Extensão Universitária, as well as reflections on the relationship between university and society. ]Keywords: University Extension, Freire,